Gut Permeability and Glucose Absorption Are Affected at Early Stages of Graft Rejection in a Small Bowel Transplant Rat Model. Issue 11 (November 2017) - Stringa, Pablo; Romanin, David; Lausada, Natalia; Papa Gobbi, Rodrigo; Zanuzzi, Carolina; Martín, Pedro; Abate, Juan Cruz; Cabanne, Ana; Arnal, Nathalie; Vecchio, Leandro; Milesi, Verónica; Portiansky, Enrique; et al.
Abstract : Background: Intestinal transplantation (ITx) faces many challenges due to the complexity of surgery and to the multiple immunological reactions that lead to the necessity of rigorous follow-up for early detection of acute cellular rejection (ACR). Our aim was to determine the kinetics of ACR using an experimental ITx model, with emphasis in the characterization of the process using different approaches, including the use of functional assays of absorptive and barrier function. Methods: ITx in rats conducting serial sampling was performed. Clinical monitoring, graft histology, proinflammatory gene expression, and nitrosative stress determination were performed. Also, glucose absorption, barrier function using ovalbumin translocation, and contractile function were analyzed. Results: The model used reproduced the different stages of ACR. Allogeneic ITx recipients showed signs of rejection from postoperative day (POD) 5, with increasing severity until 12 POD. Histological evaluation showed mild rejection in early sampling and severe rejection at late stages, with alterations in all graft layers. IL-6, CXCL 10, IFNg, and nitrite plasmas levels showed behavior coincident with histopathology. Remarkably, allogeneic grafts showed a marked alteration of glucose absorptive capacity from POD 5 that was sustained until endpoint. Coincidently, barrier function alteration was evidenced by luminal ovalbumin translocation to serum. Contractile function was progressively impaired along ACR. Conclusions: Glucose absorption and barrier function are altered at early stages of ACR when histological alterations or gene expression changes were much subtle. This observation may provide simple evaluation tools that could be eventually translated to the clinics to contribute to early ACR diagnosis. Abstract : Supplemental digital content is available in the text.